Pengembangan Sistem Pelayanan Publik Melalui Sistem Administrasi Kependudukan Menggunakan Metode Extreme Programming - Juli Budi Satya; Lilik Suhery; Alfry Aristo Jansen Sinlae; Uliyatunisa Uliyatunisa (STMIK Budi Darma, 2021)
Population administration is a public service system for the community in providing services regarding population needs. The problem that often occurs is related to data storage. Files sent by the public to take care of administration in the form of hard copies are vulnerable to loss and damage if they are not stored and archived properly. In addition, the public cannot monitor the extent to which the files they submit, whether their files are appropriate or not or complete or not. This study aims to develop a public service system through a population administration system using the development of an extreme programming (XP) system. XP is used because it is able to develop systems with needs that change very quickly. The population administration system that is managed is the administration related to births, deaths and changing of domiciles. The system was developed web-based, so that it can be used anywhere and anytime. In addition, the system developed is equipped with file monitoring facilities, so that the public can easily find out from the files or data submitted. The resulting application is in the good category, because based on usability testing shows an average value of 88% in the good category, so the application is feasible to use and as needed.